(untitled) (Global Journal of Science Frontier Research, 2018)
Weeds are the principal limiting biological factor in national rice production, with losses that vary from region to region, depending on the cultivation system, predominant weed communities and weed control methods employed by the farmers. Therefore, the experiment was conducted in Bench Maji Zone at Guraferda Woreda, during the 2017 main cropping season to investigate the effect of Bispyribacsodium 10% SC, and 2, 4-D amine salt on weeds growth, yield components and yield of rice and to investigate the possibilities of supplementing low doses of herbicides with hand weeding for effective and cost effective weed management. There were 12 treatments comprising: Bispyribac-sodium 10% SC (20 g ha-1 ,25 g ha-1,30 g ha-1), 2, 4-D amine salt (0.75 L ha-1,1.0 L ha-1 , 1.25 L ha-1), Bispyribacsodium 10% SC 20 g + 2, 4-D amine salt 0.75 L ha-1, Bispyribac-sodium 10% SC 10 g + 2, 4-D amine salt 1.0 L ha-1, Bispyribac-sodium (20 g ha-1) + hand weeding and hoeing at 35DAE , 2, 4-D amine salt (0.75 L ha-1) + hand weeding and hoeing at 35DAE, Weed free and Weedy checks. The design of the experiment was RCBD with three replications. The majority of the weeds in the experimental fields were broadleaved, grassy and sedges.